Semantic, Stylistic and Linguostatistical Features of Verbal Vocabulary in the Text (Based on the Poetry of Olzhas O. Suleimenov) - Nadejda Umbetova (CV. Media Digital Publikasi Indonesia, 2026)
Verbal vocabulary constitutes one of the most dynamic components of poetic discourse, serving not only as a grammatical category but also as a powerful means of expressing movement, emotion, cognition, and artistic imagery. In modern linguistic research, the study of verbal lexicon integrates semantic, stylistic, and quantitative approaches to reveal how poets construct conceptual meanings and aesthetic effects through verbal choices. This article investigates the semantic, stylistic, and linguostatistical characteristics of verbal vocabulary in the poetry of Olzhas O. Suleimenov. A qualitative descriptive method combined with comparative semantic analysis and elements of linguostatistical observation was employed. The corpus consists of selected poems from different collections of Olzhas O. Suleimenov. A small annotated corpus was created for frequency analysis and verb classification. The analysis focuses on the semantic groups of verbs, their stylistic functions, metaphorical potential, and communicative roles in poetic discourse. The findings indicate that Suleimenov's poetic language is characterized by a predominance of dynamic action verbs, cognitive verbs, and expressive verbal constructions that intensify imagery and emotional impact. The study demonstrates that the poet's verbal system contributes significantly to the formation of national identity, historical memory, and philosophical reflection. The results may be applied in linguistic stylistics, cognitive poetics, comparative linguistics, literary criticism, and translation studies.